Performance of Uttara chicken supplemented with lemongrass (Cymbopogon citratus) and sweet orange peel (Citrus sinensis) powder (Indian Journal of Animal Production and Management, 2024)
The purpose of the study was to investigate  the effects of supplementing lemongrass  (Cymbopogon citratus) and sweet orange peel  (Citrus sinensis) powder on the growth performance  of Uttara chicken. A total of 160-day-old Uttara chicks were randomly divided into four treatment  groups, each consisting of 40 chicks with four  replicates per treatment. The chickens were fed  different diets: a control diet in treatment T0, 0.5%  lemongrass powder in treatment T1, 0.5% sweet  orange peel powder in treatment T2, and a  combination of 0.5% lemongrass powder and 0.5%  sweet orange peel powder in treatment T3. The  feeding trial lasted for 12 weeks. The results  indicated that the overall body weight gain of birds  in the 1004.08 g (T2) group was significantly higher  compared to 907.57 g (T0), 927.12 g (T1), and  882.08 g (T3). The feed intake was not affected by  either supplementing lemongrass or sweet orange  peel powder in feed. Furthermore, the results  indicated that the overall feed conversion ratio of  birds in the 2.86 (T2) group was significantly better  compared to 3.16 (T0), 3.10 (T1), and 3.26 (T3).  The study concluded that supplementing with sweet  orange peel (T2) had beneficial effects on body  weight gain and FCR in Uttara chickens, suggesting  its use as a feed supplement for improved  profitability.
Keywords: growth traits; lemongrass powder; orange peel powder; Uttara chicken